MARKETING MIX AND STUDENT ENROLLMENT IN THE FACULTY OF ECONOMICS AND MANAGEMENT IN A PUBLIC UNIVERSITY - Heng, Chanbolin; Prum, Dr. Sokun (jfpublisher, 2025)
In a market with intense competition, student preferences may change often in higher education. Understanding what prospective students need is crucial, especially for public universities. The marketing mix has become a crucial component in helping higher education institutions succeed. The purpose of this study was to examine the relationship between seven elements of marketing mix and student enrolment in the faculty of economics and management of a public university in Cambodia. Three hundred and sixty students in the Faculty of Economics and Management at Royal University of Law and Economics, which is a prestigious public administrative university in Phnom Penh, were selected to be a sample for the study. The data was collected through administered survey from July 1st to August 15th, 2024. By applying the multiple regression analysis equipped with SPSS 22, the results found that product, place and process positively and significantly influenced on student enrolment, while other four elements including promotion, people and physical evidence had a positive and insignificant effect and, furthermore, price had a negative but insignificant impact on the faculty selection of students. Adoption of the marketing mix is thought to greatly increase student enrollment. In order to enlarge student decision in enrollment in the faculty, the study suggested that the university be encouraged to employ proper price, promotion, people and physical evidence.